A high-quality Chromosome-level reference genome assembly of white-lipped deer (Przewalskium albirostris) - Yuangang Yang; Bin Li; Wei Luo; Bo Xu; Peng Luo; Tongzuo Zhang; Zhangqiang You (Scientific Data)
Abstract White-lipped deer (Przewalskium albirostris) is the sole species in the genus Przewalskium of the Cervidae family. And it is exclusively found in the Qinghai-Tibet Plateau, where it has evolved as a specialized deer on account of the extreme climates and geographical conditions. However, limited research on the genome of this species exists. Here, PacBio and Hi-C sequencing data were constructed to a high-quality Chromosome-level reference genome for the white-lipped deer. The assembly, totaling 2.99 GB, is composed of 34 chromosomes (32 autosomes and X, Y chromosomes), with a scaffold N50 length of 76.18 Mb. Furthermore, it achieved scores of 98.4% and 63.8 in Universal Single-Copy Ortholog (BUSCO) and quality value (QV), respectively. Subsequently, employing the egapx software for genome structural annotation, we identified a total of 21909 protein coding genes, annotating 21859 of them. The high-quality and completeness of our genome sequence and annotation was affirmed by these results. The assembly will significantly contribute to enhance the understanding of the adaptation mechanisms of the white-lipped deer to the extreme environments.